2010
DOI: 10.1590/s0103-84782010000100040
|View full text |Cite
|
Sign up to set email alerts
|

Células-tronco mesenquimais

Abstract: Células-tronco mesenquimaisMesenchymal stem cell RESUMO Dentre todas as células-tronco estudadas até o presente momento, as mesenquimais (MSC) destacam

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
15
0
23

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 42 publications
5
15
0
23
Order By: Relevance
“…The observed bone growth interruption lines show abrupt discontinuation of osteoid matrix production and subsequent recovery, as described previously 13,27 . However, in this study, no local inflammatory infiltrate was observed, but only coarse and porous trabecular formation, without osteoblasts.…”
Section: ■ Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The observed bone growth interruption lines show abrupt discontinuation of osteoid matrix production and subsequent recovery, as described previously 13,27 . However, in this study, no local inflammatory infiltrate was observed, but only coarse and porous trabecular formation, without osteoblasts.…”
Section: ■ Discussionsupporting
confidence: 80%
“…It is evident that angiogenesis is evident in the trabecular bone, indicative of the acute phase of bone repair, with osteoid matrix structuring of immature braided osteophyte immediately adjacent to the blood vessels and massive infiltration of active osteoblasts, suggesting that they are responsible for matrix deposition. These characteristics suggest an intensification of the bone repair process, in the remodeling phase, since no inflammatory infiltrate was identified, as described previously 13,27 .…”
Section: ■ Discussionsupporting
confidence: 79%
See 3 more Smart Citations